Viral and inflammatory markers in cerebrospinal fluid of patients with HIV‐1‐associated neurocognitive impairment during antiretroviral treatment switch. Issue 6 (27th February 2015) - Tiraboschi, JM; Muñoz‐Moreno, JA; Puertas, MC; Alonso‐Villaverde, C; Prats, A; Ferrer, E; Rozas, N; Maso, M; Ouchi, D; Martinez‐Picado, J; Podzamczer, D
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to evaluate HIV‐1 viral load (VL) and inflammatory markers in cerebrospinal fluid (CSF) and neurocognitive performance in patients with neurocognitive impairment (NCI) while they were receiving tenofovir (TDF)/ emtricitabine (FTC)/efavirenz (EFV) and after switching to a regimen with enhanced central nervous system (CNS) penetrability. Methods This was a prospective, single‐arm pilot study. HIV‐1‐infected patients with plasma viral suppression and HIV‐associated NCI on a regimen including TDF/FTC/EFV were switched to abacavir (ABC)/lamivudine (3TC)/maraviroc (MVC). The Global Deficit Score (GDS) was used to score cognitive function at baseline and 48 weeks after treatment switch. Both CSF and blood samples were taken at baseline and between weeks 24 and 36 after switching. HIV‐1 RNA in plasma and CSF was determined by quantitative reverse transcriptase−polymerase chain reaction (qRT‐PCR). Inflammatory biomarkers in CSF were measured by enzyme‐linked immunosorbent assay (ELISA). Results A total of 71 patients receiving TDF/FTC/EFV were screened. Twelve of them (17%) had documented NCI, lacked the human leucocyte antigen (HLA)‐B*57:01 haplotype and harboured Chemokine Receptor Type‐5 (CCR5)‐tropic virus. Eight patients had detectable HIV‐1 RNA (between 2.7 and 41.6 HIV‐1 RNA copies/mL) in CSF at baseline. All participants had elevated levels of neopterin and Monocyte Chemoattractant Protein 1 (MCP‐1) in CSF at baseline. Eight out of 12 patients completed their follow‐up assessment after treatment switch. The GDS decreased from 0.55 to 0.4 (P = 0.085). Median HIV‐1 RNA in CSF decreased from 3.49 to 2.20 (P = 0.23). Among the inflammation markers in CSF, tumour necrosis factor (TNF)‐α decreased significantly from median 0.51 to 0.35 pg/mL (P = 0.027), showing a correlation with the changes in neopterin, interferon (IFN)‐γ and interleukin (IL)‐6. Conclusions Most patients with NCI receiving TDF/FTC/EFV had low‐level viraemia and/or increased inflammatory markers in CSF. Treatment switching to an MVC‐containing regimen with better CNS penetration resulted in a trend towards improvement in neurocognitive status and reduced TNF‐α concentrations in CSF.